Dying to live: migrant deaths and citizenship politics along European borders: transgressions, disruptions, and mobilizations. Issue 5 (3rd July 2016) - Rygiel, Kim
Abstract: Migrants and refugees continue to die as they attempt to cross into Europe. This article explores the issue of 'dying to live' to draw attention to the disturbing fact of these deaths in relation to the state, biopolitics, and citizenship, but also to the growing mobilization around refugee and migrant deaths along European borders. The article examines transnational activism in solidarity with migrants, refugees and their families in response to deaths at Europe's borders as one example of the many political struggles for greater rights undertaken by refugees, migrants, and solidarity activists emerging across Europe and elsewhere. An examination of struggles around rights of the dead and in response to migrant and refugee deaths suggests that they can be transgressive of the logic of modern citizenship.